STRUCTURE AND PROPERTIES OF CONNECTING ALKALINE ACTIVATION USING CEMENT DUST - S. A. Aliev; R. S.-A. Murtazayevа; M. Sh. Salamanova (Вестник Дагестанского государственного технического университета: Технические науки, 2019)
Objectives In the process of firing Portland cement clinker in electrostatic precipitators, in rotary kilns, a large amount of harmful substances, both clinker and aspiration, accumulates, therefore rational use of these products leads to certain shares of a full-fledged river resource, which are derived from industrial cement. It should be noted that the reuse of dust electrostatic precipitators is impossible.Method The basis for obtaining durable and more resource-efficient composites is based on modern technological methods that contribute to the improvement of technical and physicomechanical properties, with the integrated application of technogenic raw materials and liquid sodium binder.Result The basis for obtaining durable and more resource-efficient composites is based on modern technological methods that contribute to the improvement of technical and physicomechanical properties, with the integrated application of technogenic raw materials and liquid sodium binder.Conclusion The developed clinker-free binder formulations using the cement industry wastes and sodium-based sludge glass will make it possible to produce less expensive, durable, and durable composites that will partially replace traditional concrete with expensive portland cement.